Streptococcus pneumoniae endophthalmitis after exposed glaucoma drainage implant - Dylann Fujimoto; Philina Yee; Stephanie Noh; Kapil Mishra; Sameh Mosaed (American Journal of Ophthalmology Case Reports)
A patient with juvenile glaucoma status post 2 glaucoma drainage implants in each eye presents with painful vision loss in the left eye and is found to have streptococcus pneumoniae endophthalmitis from an exposed inferior glaucoma drainage implant. The infection is managed medically with intravitreal antibiotics and surgically with a glaucoma drainage device revision, anterior chamber washout and pars plana vitrectomy.